Meningkatkan Kemampuan Higher Order Thinking Skill Siswa Kelas X pada Materi Teks Wayang Melalui Project Based Learning - Wahyudi, Ahmad Rizky; Adipitoyo, Sugeng (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Higher Order Thinking Skills (HOTS) are critical for 21st-century learners, yet their development is often hindered by rote-based instructional practices, especially in Javanese language subject. This study aimed to improve the HOTS of 10th-grade students through the implementation of Project-Based Learning (PjBL) in wayang text instruction. Conducted as Classroom Action Research (CAR) at SMAN 13 Surabaya, the study involved 36 students from class X-2 over two action cycles. Each cycle followed Kemmis and McTaggart’s model: planning, action, observation, and reflection. Data were collected through observation, interviews, HOTS-based written tests, and project documentation. Results revealed a significant improvement in students’ HOTS, with post-test scores increasing from an average of 64.7 to 68.4, and the percentage of students reaching the minimum mastery level rising from 32% to 47%. Students also exhibited more active participation, stronger analytical skills, and enhanced creativity in completing their projects. The PjBL model enabled students to critically engage with wayang texts, connect them to real-life contexts, and strengthen Javanese cultural literacy. These findings affirm the relevance and effectiveness of PjBL in enhancing HOTS, supporting the goals of the Merdeka Curriculum.